Prediction of wind power with various air speed using neuro-fuzzy logic in MATLAB - Tushar, Naimur Rahman; Shuvo, Md. Tanvir Ahmed; Das, Dilip Kumar; Chowdhury, Suman (International Journal of Applied Power Engineering (IJAPE), 2025)
The energy crisis in Bangladesh has persisted for many years, predominantly reliant on fossil fuels for power generation, which is both economically and environmentally costly. It is imperative to transition away from fossil fuels towards more cost-effective and eco-friendly energy sources. Wind energy presents a viable solution to alleviate this crisis, especially considering Bangladesh's extensive coastline, offering great potential for harnessing significant amounts of electricity. Extensive research has been conducted on the feasibility of deploying wind turbines across various coastal zones to generate power and facilitate irrigation seasons. This research delves into the operational principles and performance parameters of wind turbines. A modified fan is utilized to assess power generation under varying air speeds, with data analysis conducted using neuro-fuzzy logic. The findings reveal a minimal percentage error of 0.09, underscoring the reliability of the proposed fuzzy model in predicting wind power output based on wind speed. This underscores the potential for leveraging wind energy as a sustainable and reliable alternative to fossil fuels in addressing Bangladesh's energy challenges.